6. Single-step laparoscopic cholecystectomy and endoscopic retrograde cholangiopancreatography in patients with cholecysto-choledocholithiasis - Long, Tran Bao; Dat, Trinh Quoc; Hung, Le Quang; Hung, Tran Duy; Anh, Nguyen Duc (Tạp chí Nghiên cứu Y học, 2023)
Current treatment of complicated calculous biliary disease typically involves a two-step procedure consisting of pre- or post-operative endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy (LC). This practice creates drawbacks as there is the need for two anesthesia inductions and longer hospital stay. The combination of LC and ERCP (LC + ERCP) for patients with cholecysto-choledocholithiasis has shown safety advantages, reducing anesthesia inductions and bringing high efficiency. This is a retrospective case series implemented at the Department of General Surgery - Hanoi Medical University Hospital between March 2020 and July 2022. In total, 44 patients met the criteria of this study. The average age of the cohort was 55.43 ± 18.12 years. The mean operating times of ERCP and LC were 58.05 ± 20.10 min and 54.09 ± 23.80 min, respectively. There was one intra-operative adverse event and no conversion. The mean hospital stay was 3.95 ± 2.28 days, and the rate of stones clearance was 100 per cent. LC combine ERCP in a single setting is a safe, effective procedure in treating cholecysto-choledocholithiasis.